Long‐term follow‐up and health‐related quality of life among cancer survivors with stage IEA orbital‐type lymphoma after external photon‐beam radiotherapy: Results from a longitudinal study. Issue 5 (7th August 2022) - Hoffmann, Christian; Rating, Philipp; Bechrakis, Nikolaos; Eckstein, Anja; Sokolenko, Ekaterina; Jabbarli, Leyla; Westekemper, Henrike; Mohr, Christopher; Schmeling, Claus; Huettmann, Andreas; von Tresckow, Julia; Göricke, Sophia; et al.
Abstract: We assessed the long‐term outcomes and treatment‐related adverse effects of patients with Stage I, "orbital‐type" lymphomas that were uniformly treated with photons. All consecutive patients diagnosed with low‐grade, Ann Arbor Stage IEA orbital lymphoma treated between 1999 and 2020 at our department were retrospectively reviewed. We excluded patients with exclusive conjunctival involvement, typically treated with en face electrons. In order to quantify radiotherapy related side effects we applied the CTCAE criteria, analyzed changes in visual acuity, quantified dry eye symptoms by use of the Ocular Surface Disease Index (OSDI) score and applied the EORTC QLQ‐C30 questionnaire for quality of life (QoL) assessment. In total 66 eyes of 62 patients were irradiated with a median dose of 30.6 Gy. The median follow‐up was 43.5 months. The predominant histological subtype were MALT lymphomas. No local failure occurred in this cohort. Of nine outfield relapses, six solely occurred in the contralateral eye. The 5‐ and 10‐ years distant progression free survival rates (PFS) were 81.4% and 63.5%. The 5‐ and 10‐years overall survival rates were 85.1% and 71.9% without any tumor related death. Of the acute toxicities none was higher than CTCAE grade 1. The predominant late toxicities were dry eyes (21.2%) of CTCAE Grade <2 and radiation induced cataracts (19.7%). During long‐term follow up the average visual acuity did not deteriorate. The global QoL was worst before treatment and improved significantly after 24 months ( p  = 0.007). External beam radiotherapy of "orbital‐type" lymphomas with photons is an effective and gentle treatment option with excellent local control rates. From the high control rates the trend to use slightly lower total doses of 24–27 Gy with conventional fractionation is supported. As non‐coplanar radiotherapy techniques improved and total doses can slightly be reduced, the current status of radiotherapy as first line therapy is provided.